The Poems of John Donne - Donne, John (Saga Egmont, 2022)
Soldier, secretary, Anglican priest, MP, father of 12, Dean of St Paul\'s... it\'s amazing that John Donne had any spare time. But this collection of his poems shows why it is good to give work to a busy person. \'The Poems of John Donne\' is an education and an inspiration, with his signature rhetorical style ever-present. Through love letters, songs, epigrams, satires and memorial verse, Donne reveals a breadth of knowledge and depth of understanding of the human spirit that has hardly been surpassed. This collection is perfect for fans of William Shakespeare and Alexander Pope.